Comunicação e consumo no mercado de investimentos plataformizado - Martinez, Cassio Ozires Zanforlin Bondia (2024)
This study analyzes the ecological environment of digital platforms in which the platformized investor is embedded, promoting their investments, and seeks to contribute to the field of communication and consumption by discussing the understanding of contemporary investment. To this end, the study aims to analyze how investment consumption via platforms occurs in the investor's conception through the identification of the dimensions of interference that implicate this subject; it also seeks to understand the literacies necessary for investment; and it further investigates the investor's understanding regarding the use of their data by investment platforms. Based on a qualitative approach, using in-depth interview techniques, we interviewed ten investors who make their contributions via investment platforms and analyzed, based on the authors we mobilized in this research, how investment consumption rituals occur (MCCRACKEN, 2007; PEREZ, 2020), how the investor understands financial literacies (SAVOIA; SAITO; SANTANA, 2007), media literacies (FERRÉS; PISCITELLI, 2015), and algorithmic literacies (GILLESPIE, 2018), which together, in our perspective, promote platform literacy. Thus, in light of these issues and drawing from authors such as José Van Dijck (2017, 2019, and 2022) and Neil Postman (1994), we utilized the perspective of Media Ecology theory to formulate an ecological understanding of platforms, named and materialized in this research as the Ecology of Investment Platforms. Finally, we observed that, within a circuit of platforms, the investor is implicated by global, political, and social forces, such as liberalizing logics, mediatization, and platformization, as well as being involved in an affective circuit that occurs within the platforms. In this way, the investor is alienated and depends on their level of literacy to be able to promote their investments critically and autonomously.